Design of Human Motion Signal Gathering System Based on USB 2.0 - Yongheng Bai (International Journal Bioautomation, 2018)
In order to design a human motion signal acquisition system, through the virtual hardware platform, the firmware and the driver program of the data acquisition system are designed, so it can run in computers with Windows 7 and Lab Windows/CVI platform. At the same time, the 12-bit A/D conversion chip with high sampling rate and high precision is used for A/D conversion circuit design. In addition, the multi-channel technology is used to realize A/D conversion of multiplexing signal, which improves the measurement accuracy of the system. The results showed that this research implemented the advantages of USB 2.0 interface, improved the data serial transmission speed and met the high data throughput requirements. To sum up, the system achieves the design of human motion signal acquisition system with high efficiency, convenience, low cost and high-performance price ratio.